2015
DOI: 10.1080/10803548.2015.1095546
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of accident severity in the construction industry using the Bayesian theorem

Abstract: The findings provide a direction for more effective safety strategies and occupational accident prevention and emergency programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Building construction workers are also generally exposed to an excessive risk of being injured at work (Almen Larsson and Thunqvist, 2012). Alizadeh, Mortazavi and Sepehri (2015) acknowledged that in construction, workers perform a great diversity of activities, each one with a specific associated risk. Zavadskas, Turskis and Tamošaitiene (2010), Kozlovská and Struková (2012) and Muiruri and Mulinge (2014) also agreed that many construction activities inherently possess high health and safety risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Building construction workers are also generally exposed to an excessive risk of being injured at work (Almen Larsson and Thunqvist, 2012). Alizadeh, Mortazavi and Sepehri (2015) acknowledged that in construction, workers perform a great diversity of activities, each one with a specific associated risk. Zavadskas, Turskis and Tamošaitiene (2010), Kozlovská and Struková (2012) and Muiruri and Mulinge (2014) also agreed that many construction activities inherently possess high health and safety risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…SSCPs are associated with S&H risks [13,28], and the results of ANN modeling in the present study indicated that some RMFs could also predict AFR, including HAZID, periodic risk assessment, development and implementation of risk control measures, and housekeeping. Moreover, some researchers have reported that the most important influential factors in SSCP accidents are the weaknesses of the S&H risk management systems, such as the deficiencies in HAZID, risk assessment, and risk control [22,29,30].…”
Section: Feature Selectionmentioning
confidence: 51%
“…1) Impact scale (I) with categories 1 -3. The scales used for measuring impact (I) with categories 1 -3 were found in up to 4 reference sources [4,[9][10][11]. The impact scale with categories 1 -3 has been described in Table 1.…”
Section: Risk Impact Categorization Scalementioning
confidence: 99%